2019
DOI: 10.3390/ma12030381
|View full text |Cite
|
Sign up to set email alerts
|

Naturally-Derived Biphasic Calcium Phosphates through Increased Phosphorus-Based Reagent Amounts for Biomedical Applications

Abstract: Calcium carbonate from marble and seashells is an eco-friendly, sustainable, and largely available bioresource for producing natural bone-like calcium phosphates (CaPs). Based on three main objectives, this research targeted the: (i) adaptation of an indirect synthesis route by modulating the amount of phosphorus used in the chemical reaction, (ii) comprehensive structural, morphological, and surface characterization, and (iii) biocompatibility assessment of the synthesized powdered samples. The morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…The maximum temperature used in this study (215 °C) has a defining influence on the of both polymer types revealed specific peaks of the HA main elements, especially Ca and P [44]. The 192 presence of the carbon peak in the spectra denotes the existence of the polymeric substrate.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…The maximum temperature used in this study (215 °C) has a defining influence on the of both polymer types revealed specific peaks of the HA main elements, especially Ca and P [44]. The 192 presence of the carbon peak in the spectra denotes the existence of the polymeric substrate.…”
mentioning
confidence: 84%
“…The present research involved preliminary studies on PLA and TPU filaments with modified core (polymer)-shell (ceramic) structure. These studies were based on morpho-compositional analysis, given that coating morphology is a must-criteria and the most important factor for the targeted materials along with chemical composition [44].…”
Section: Morpho-compositional Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The sharp and well-split IR absorption bands of orthophosphate groups recorded in the case of the Bio-HA film (Figure 6a) testified for it its high crystallinity [69], in full agreement with the XRD data. All the characteristic IR bands of HA were evidenced for the Bio-HA sputtered structure: ν 4 bending (~565 and~600 cm -1 ), ν 1 symmetrical stretching (~962 cm −1 ), and ν 3 asymmetric stretching (~1032 and~1088 cm -1 ) vibration modes of orthophosphate groups, and ν L libration (~632 cm -1 ) and ν S stretching (~3753 cm -1 ) of structural hydroxyl units [26,36,69]. Only slight shifts and intensity modification of the Bio-HA film bands (Figure 6a) with respect to the pure HA reference and Bio-HA source powder (Figure 6b) were noticed.…”
Section: Functionalization Of the Cranial Mesh With A Bioceramic Layermentioning
confidence: 99%
“…This is why the extraction of Bio-HA from animal bones could represent a viable solution, not only due to the intrinsic natural doping with ions which can promote specific biofunctional traits, but also due to their high availability and reduced costs [17,20]. For biomedical research purposes, bovine [21,22], ovine [23], or swine bones [24] are the most commonly used resources, but also fish [25] and sea-shells [26], as well as more exotic sources such as camel [27] or shark [28] have been explored. For depositing calcium phosphate-based coatings onto metallic implants, the industrial technique of choice is plasma spray (PS), due to the deposition speed, large area coverage, and inexpensive working atmosphere (i.e., ambient or argon) [29,30].…”
Section: Introductionmentioning
confidence: 99%